A divulgação de espetáculos teatrais na pós-modernidade : as estratégias de comunicação na produção cultural das artes cênicas - Gotardo, Suelen (2021)
Theater spectacle need communication to develop dissemination objectives and thus reach their audience, especially in the post-modern context: pluralist and collective. On the other hand, the society of the spectacle, technological and connected, proposes that cultural producers investigate new ways of thinking about cultural management. Moved by this purpose, this research uses the key notions of the imaginary to understand how theater groups work with cultural production to access the contemporary spectator. This paper reflects the participation of communication in the theatrical dissemination process, based on the analysis of four different theater show in the city of Porto Alegre, in 2019, applying the technique of content analysis (Bardin, 2011): TOC - Uma Comédia Obsessiva Compulsiva; 2068; Em Chamas e Alice - Além da Toca do Coelho. In order to support our arguments, we use reflections of Michel Maffesoli, Gilbert Durand, Juremir Machado da Silva, Gilles Lipovetsky, Guy Debord, Denis Guénoun, Linda Bulik, Linda Rubim, Rosa Villas-Boas and Nadja Magalhães Miranda are used to support this path. The work offers reflections on cultural production, in addition to exploring the contemporary context of theater industry in the capital of Rio Grande do Sul. A look at the transversality of the areas of communication and performing arts.